Answer:
We conclude that:
h(f(-1)) = -2
∴ option D i.e. -2 is correct.
Explanation:
Given
f(x) = 4x² - 1
g(x) = 1/2x + 5
h(x) = 2(x - 4)³
To determine
h(f(-1)) = ?
In order to determine h(f(-1)) first we need to determine f(-1).
substitute x = -1 in the function f(x) = 4x² - 1
f(-1) = 4(-1)² - 1
f(-1) = 4(1) - 1
f(-1) = 4-1
f(-1) = 3
so
h(f(-1)) = h(3)
now substitute h = 3 in the function h(x) = 2(x - 4)³
h(x) = 2(x - 4)³
h(3) = 2(3 - 4)³
h(3) = 2(-1)³
h(3) = 2(-1)
h(3) = -2
Thus,
h(f(-1)) = h(3) = -2
Hence, we conclude that:
h(f(-1)) = -2
∴ option D i.e. -2 is correct.